Preservation of Carrion Flowers as an Ecotourism Attraction in Bogor Botanical Garden - Pradini, Gagih; Kusumaningrum, Anisa Putri; Agustiani, Fitri; Ardira, Maya Ayu; Waluyo, Tri (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2023)
In Bogor City, there is a large botanical garden that can help us learn about various kinds of trees and plants in the world called "Bogor Botanical Garden". It covers an area of 87 hectares and has 15,000 types of tree and plant collections. In ecotourism, the use of energy-saving resources is prioritized, such as solar power, wooden buildings, recycled materials, and other environmentally friendly materials. Conversely, ecotourism activities are sought not to sacrifice the preservation of flora and fauna, but not to change the topography of the land, for example by erecting buildings that are foreign to the environment and culture of the local community. This research uses qualitative and descriptive approach research methods. Qualitative research is research that is descriptive and tends to use analysis. Process and meaning are highlighted in qualitative research. The theoretical foundation is used as a guide so that the focus of research is in accordance with the facts in the field